CONTROL OF THE AIRCRAFT FLIGHT VELOCITY VECTOR BASED ON THE ENERGY APPROACH - V. P. Kharkov; S. P. Khalyutin (Научный вестник МГТУ ГА)
This paper presents a method of the aircraft flight velocity vector control synthesis taking into account constraints on the thrust of the power plant, the restriction is made on the basis of the use of the power triangle, representing an equilateral triangle whose height is interpreted as the thrust of the power plant. The control laws are synthesized based on the method of inverse dynamics problems.